Physiological response of dual-purpose sorghum bicolor l. To water stress and its significance in forage and grain production in crop-livestock systems (Bangladesh Journal of Botany, 2026)
Under the severe situation of frequent extreme droughts caused by global climate change and the continuous expansion of agricultural water shortage gaps, the traditional high-water-consuming crop cultivation model is facing significant sustainability challenges. Exploring the production potential of crops with high water use efficiency has become key to ensuring food security. Dual-purpose sorghum (Sorghum bicolor L. Moench), a C4 crop that can provide both grains and high-quality feed, has become a cornerstone for building climate-smart agriculture in arid regions due to its excellent drought and salt resistance as well as high biomass potential. By combining meta-analysis with system dynamics simulation, a physiological-agronomic coupled model of sorghum's response to water stress is developed in this study. At the physiological level, drought-tolerant genotypes synergistically upregulate antioxidant enzymes while maintaining a proline-centered osmotic regulation network, and the coupling between photosynthetic rate and stomatal conductance follows a nonlinear modified Farquhar model. At the agronomical level, severe drought reduces aboveground biomass by approximately 37% but significantly increases the root-to-shoot ratio, reflecting a survival-first resource allocation strategy. Introducing the brown midrib genotype effectively counteracts drought-induced lignification that reduces feed digestibility. Monte Carlo economic simulation reveals that integrated crop-livestock systems based on sorghum have net income fluctuation 45% lower than single-crop cultivation, demonstrating strong economic adaptability. This study provides theoretical and practical guidance for optimizing sorghum germplasm utilization and achieving sustainable collaborative production of grains and feed.Bangladesh J. Bot. 55(2): 311-320, 2026 (June)